2016
DOI: 10.1615/intjmedmushrooms.v18.i9.10
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of Biocompounds from Spores of the Lingzhi or Reishi Medicinal Mushroom Ganoderma lucidum (Agaricomycetes): A Review

Abstract: Ganoderma lucidum is a well-known representative of mushrooms that have been used in traditional Chinese medicine for centuries. New discoveries related to this medicinal mushroom and its biological properties are frequently reported. However, only recently have scientists started to pay special attention to G. lucidum spores. This is in part because of the recent development of methods for breaking the spore wall and extracting biocompounds from the spore. Although some research groups are working with G. luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…These two extraction methods were more effective in isolating a major heterogeneity of monosaccharaides (table 5). The monosaccharides found corresponded to those reported by Yue et al [28] and Soccol et al [29], the majority being identified as glucose, mannose, and galactose. Fucose and arabinose were absent in the control extract.…”
Section: Protein Polyphenol Carbohydrate and Antioxidant Contentsupporting
confidence: 85%
See 1 more Smart Citation
“…These two extraction methods were more effective in isolating a major heterogeneity of monosaccharaides (table 5). The monosaccharides found corresponded to those reported by Yue et al [28] and Soccol et al [29], the majority being identified as glucose, mannose, and galactose. Fucose and arabinose were absent in the control extract.…”
Section: Protein Polyphenol Carbohydrate and Antioxidant Contentsupporting
confidence: 85%
“…For this reason, various methodologies have been developed to break G. lucidum spores, including ultrasonication, ultra-fine grinding, high-speed centrifugal grinding, shear grinding, and enzymatic grinding. These have provided between 80 and 100% breaking efficiency [6][7][8][26][27][28][29]. Nevertheless, they require complex equipment, whereas maceration with steel/chrome spheres provides an easier, more economical way to fragment G. lucidum spores, as reported in the present study.…”
Section: Breaking Of Ganoderma Lucidum Sporessupporting
confidence: 60%
“…Ganoderma lucidum contains polysaccharides, triterpenes, sterols and other biologically active compounds, which have immunomodulatory, anticancer and anti-pathogenic effects (Cor et al 2018). Ganoderma lucidum spores contain active ingredients similar to those of G. lucidum, but the content of the major ingredients including polysaccharides and triterpenic acid is relatively higher and displays more prominent biological activities (Xie et al 2013;Soccol et al 2016). Existing studies have not systematically investigated the lipid-lowering and anti-AS effects of G. lucidum spores.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ganoderma lucidum ( G. lucidum ) exhibited preventive and therapeutic effects in cancer ( 15 ), chronic bronchitis ( 16 ), bronchial asthma ( 17 ) and hepatitis ( 18 ). Polysaccharides, which consist of glucose, mannose, galactose, xylose, fucose and arabinose, are one of the most important active components of G. lucidum ( 19 ). Several in vitro and in vivo studies have demonstrated that polysaccharides extracted from G. lucidum (GLP) exhibited significant effects on tumorigenesis, oxidative stress, inflammation and immunoregulation ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%